(untitled) - Campbell, Kathy (Hersley, PA, 2004)
Text is a combination manual/workbook that leads users through the steps of preparing effective content for the Web and display media such as electronic slide shows. For post-secondary institutions and learning organizations who are developing e-learning resources. Softcover, hardcover available. DLC: Education, Higher--Electronic information resources.
Keywords: Education, higher,Internet in education,Education, higher; Electronic information resources,Computer-assisted instruction